(3TQM GdeTGcd ef OjhGf GdeJfHi hCHi JeGes - (3GdeHGQc Hf CMeO Hf GdeHGQc Hf ehghH GddNej GdEQHdj, GdeYQha HGHf GdeSJhaj,J (B637 (3g` s
(3BNQgG (B:s
(3JfJgi HCKfGA MQa GdOGd s
(3fSNI eQJHg Ydi MQha GdeYLes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B269 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B170s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B21 - (3U (B493 s
(3eUOQ GbJfGA GdCUd (B:s
(3ShgGL (B((3COH (B135) s
Keywords: (3GdCOHs